Implementation of Pentahelix Collaboration Model in the Development of Government Institution’s Potency as General Services Agency - Tri Astuti Wisudayati; Dian Charity Hidayat; Kresno Agus Hendarto (Foresty Faculty of Hasanuddin University, 2020)
The maturity of the R&D institutions through Public Service Agency (BLU) is an effort to increase the relevance in responding stakeholder needs. BLU is present as a solution for R&D institutions in providing goods and/or services that are sold based on the principles of efficiency and productivity. However, the strategic plan for the BLU formation is prepared by submitting a substantive, a technical and an administrative requirement. Therefore, this research facilitates thesubmission of these requirements throughthe Pentahelix Collaboration Model, whichis the optimization of 5 (five) roles: business, government/management, community, researchers and mediaby implementing the roadmap at the Forest Tree Seed Technology Research and Development Center. Thecase study steps to improve all the roles conditions was by adapting Kurt Lewin's action research into 4 (four) stages: planning, action, observation, and reflection. The role of the business unit is emphasized on market differentiation and business strategy by considering an opportunity to increase revenue realization/financial forecasting ratio. The role of management is emphasized on budget flexibility and remuneration by considering cost accounting and its unit cost calculations. The role of the community is emphasized on the conducive policies by accommodating stakeholders’need. The role of the researcher is emphasized on the innovation of forest seed’s products/services by improving service quality and managing it with corporate style principles. The role of the media is emphasized on the professionalism of human resources by considering the community satisfaction index.